Responses of mesophilic anaerobic sludge microbiota to thermophilic conditions: implications for start-up and operation of thermophilic THP-AD systems - Zhang, Liang (2022)
Anaerobic digestion (AD) has been widely employed for wastewater and organic waste treatment, in which methanogenesis is highly driven by close microbial interactions among intricate microbial communities. However, the ecological processes underpinning the community assembly that support methanogenesis in such engineered ecosystems remain largely unknown, especially when exposed to challenging circumstances (e.g., high temperature, ammonium content). Here, eight AD bioreactors were seeded with four different inocula (two from full-scale mesophilic AD systems and the other two from lab-scale mesophilic AD systems), and were operated under thermophilic conditions (55 °C) for treating thermal hydrolysis process (THP) pre-treated waste activated sludge to investigate how mesophilic community responds to thermophilic conditions during the long-term cultivation. Results showed that the inocula collected from the full-scale systems were more resilient than that from the lab-scale systems, which may be primarily attributed to indigenous robust methanogens. As a result, the former efficiently generated methane which was predominantly contributed by Methanothermobacter and Methanosarcina (healthy AD ecosystem), while methanogenic activity was remarkably prohibited in the latter (dysfunctional AD ecosystem). Thermophilic environment was a strong selection force, resulting in the convergence of microbial communities in both the healthy and dysfunctional AD ecosystems. Deterministic processes predominated the community assembly regardless of AD ecosystem function, but stronger influences of stochastic processes were observed in dysfunctional AD ecosystems, which was likely attributable from the stronger effect of immigrants from the feedstock. As indicated by molecular ecological network analysis, the microbial network structures in the healthy AD ecosystems were more stable than those in the dysfunctional AD ecosystems. Although keystone taxa were different among the bioreactors, most of which played vital roles in organic hydrolysis/fermentation. To sum up, this study greatly improved our understanding of the relationships between microbiological traits and AD ecosystem function under thermophilic conditions, which could provide useful information to guide thermophilic AD (e.g., THP-AD) start-up and health diagnosis during operation.